(untitled) (Journal of Academic Research, 2019)
The study points out to show the important rule of information technology in selecting building bricks which are different among each other in terms of thermal insulation. In this study, three locally common types of building bricks have been chosen which are (cemented hollow brick, limestone brick and perforated brick). The study has been performed on the building of Intermediate Institute of Mechanical and Electrical Professions in the city of Tarhona which is composed of one floor and twenty six spaces. The data of geographic location of the building were interned to calculate the thermal loads using the program HAP4.9 since the building material will change as well as the external color of the wall with maintaining all other thermal loads constant. This is to compare the three chosen materials. The obtained results were good since this study has proved the confidentiality of program HAP4.9 in calculating thermal loads of materials and trading off them.